Formulating Oil Emulgel of Nyamplung (Calophyllum inophyllum L) with Variations of HPMC and Activity Testing for Incision in Rabbit New Zealand - Erinda Risma Puspita Cahya; Dewi Ekowati; Dwi Ningsih (Indonesian Journal of Pharmaceutical Education, 2022)
Emulgel is an emulsion of both O/W and W/O which is made into a gel by mixing it with a gelling agent. One of the gelling agents that is often used is HPMC because it can produce a clear gel, easily soluble in water, and has low toxicity. Nyamplung oil has wound healing activity by stimulating cell proliferation and the production of collagen and GAG (glycosaminoglycans). The purpose of this study was to find out that nyamplung (Calophyllum inophyllum L) oil can be made into a good emulgel preparation, has the effect of healing cuts, to determine the effect of variations in HPMC concentration on the physical quality and stability of the emulgel, and in accelerating the healing of cuts. This study used three formulas containing 1%, 2%, and 3% HPMC plus one control formula. Emulgel is made by mixing emulsion with gel and contains 1% nyamplung oil, then physical quality tests are carried out : organoleptic, homogeneity, pH, adhesion, dispersibility, viscosity test, emulgel type test, stability test. The wound healing activity test was carried out on the back of New Zealand rabbits. The percentage of treatment results were statistically analyzed. The results showed that all nyamplung oil emulgel formulas could be made ini emulgel preparations, had good physical quality and stability and had the effect of wound healing. The effect of gelling agent concentration affects the speed of wound healing. The result of the most optimal wound healing activity test is the formula 2.